2019
DOI: 10.3390/w11051033
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on Motion and Resistance Characteristics of the Partial Air Cushion Supported Catamaran

Abstract: The Partial Air Cushion Supported Catamaran (PACSCAT) is an innovative design which combines both the characteristics of hovercraft and catamaran. Further, it provides a high-speed and efficient solution with excellent performance, particularly for shallow water. In this paper, experimental and numerical method are carried out for research of motion attitude and resistance characteristics, which provide a reference for further research and hull optimization work. By model towing test and data interpretation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Taking the edge wall roughness of the glass flume in the test as n w = 0.01, then the vegetation roughness n b can be calculated from Equations ( 17)- (21). The relationships between the vegetation roughness coefficient n b , water flow rates Re and Fr, and vegetation sedimentation thickness were studied experimentally.…”
Section: Vegetation Roughness Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the edge wall roughness of the glass flume in the test as n w = 0.01, then the vegetation roughness n b can be calculated from Equations ( 17)- (21). The relationships between the vegetation roughness coefficient n b , water flow rates Re and Fr, and vegetation sedimentation thickness were studied experimentally.…”
Section: Vegetation Roughness Coefficientmentioning
confidence: 99%
“…Their results showed that the resistance coefficient of non-submerged willow branches increased linearly with water depth, and under the same arrangement, the resistance coefficients of branches with subbranches were 2~3 times those without. Lu et al [21] studied the change rules of vegetation resistance coefficients under different vegetation densities, flow conditions, and water depths. They adopted the vegetation hydraulic radius as the characteristic length to represent vegetation and the Reynolds number to represent flow conditions when examining the relationship between the vegetation resistance coefficient and flow.…”
Section: Introductionmentioning
confidence: 99%